Meconium-stained amniotic fluid as a risk factor for perinatal asphyxia - Mehta, Vidhi; E., Adarsh; ., Spoorthi; ., Archana; Hassan, Muhammed (International Journal of Contemporary Pediatrics, 2019)
Background: The aim of this study was to find out immediate fetal outcome in meconium-stained amniotic fluid in relation to perinatal asphyxia. Methods: This retrospective study includes medical records of all neonates admitted to Neonatal Intensive Care Unit (NICU) between December 2016 and July 2018. The variables reviewed are age, sex, weight, mode of delivery, gestational age, presence of meconium aspiration syndrome (MAS) and perinatal asphyxia. Results: Out of 408 total admissions in NICU, 69.1% were male babies and remaining 30.9% were female babies. In the study out of 36 subjects with Perinatal Asphyxia, 38.9% had MAS and 61.1% had not MAS. Out of 372 subjects without perinatal asphyxia, 93.8% had no MAS and 6.2% had MAS. There was significant association between MAS and perinatal asphyxia. Odds ratio was 9.656. i.e. those with MAS had 9.656 times higher risk for perinatal asphyxia. Conclusions: The management of MAS, which is a perinatal problem, requires a well concerted and coordinated action by the obstetrician and pediatrician. Prompt and efficient delivery room management can minimize the sequelae of aspirated meconium and decrease the chance of perinatal asphyxia in the new born babies.